Understanding human perception of field hockey stick performance - Carre, M.; McHutchon, M. (The Engineering of Sport 6, Volume 3 Developments for Innovation, 2006)
This study applies the semantic differential approach to measure hockey players` emotional responses to different hockey sticks, based on factors relating to performance (e.g. comfort, power, control) as well as physical properties (e.g. weight, stiffness). Each player was given a set of disguised sticks and asked to carry out a set of ball-strikes, before rating the sticks using a semantic differential questionnaire. The hockey sticks varied in their physical properties and results indicated that although players were unable to perceive stick stiffness directly, they were able to perceive the effect of stiffness through their rating of comfort and power. Perception of stick `weight` was strongly linked to the reaction torque felt at the hand when the stick was held in equilibrium, prior to a hit. Sticks judged in a positive light were also reported to be comfortable and powerful and had relatively high rigidity. Results from this study have been incorporated into an all-encompassing design methodology for sports equipment, including analytical and empirical models of equipment performance.